FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA BAGIAN PRODUKSI UNIT CLHOR ALKALI PT. IKPP PERAWANG Tbk TAHUN 2016 - yusmardiansah yusmardiansah (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
The Usage of PPE is the last stage. If technician control and administration can not run well..So, using this PPE is important. Infact, Chlor Alkali unit PT.IKPP with it,s high level of risk but there are still many worker do not use the PPE.The objective of this research is to analyze factors related to workers behavior in using PPE PT.IKPP year 2015. This study was an observational with cross sectional design. The instrument used was a questionaire to see the characteristics of the respondent, with 110 workers. And too for variable other.DataÂ  are analyzed by using chi-square.The result of the research showed that there were 45,5% of workers used PPE and 54,5% did not. Bivariate analysis it is known that supervising variable only have siqnificant relation with the use of PPE. On the other side variable; perseption of risk, cognition and policy did not siqnificant relation with the use of PPE.Referring to the resulth of this research, I advise that management should maintenance and improve supervising system intenly. And then management should improving education or knowledge about hazard potensial as well as training and activity others. So, workers use of PPE not because supervising only, but they caused by awareness.